Recent Advances in the Development of Antibiotics-Coated Gold Nanoparticles to Combat Antimicrobial Resistance - Partha Pratim Sarma; Akhilesh Rai; Pranjal K. Baruah (MDPI AG, 2024)
Antimicrobial resistance (AMR) has become an alarming threat to the successful treatment of rapidly growing bacterial infections due to the abuse and misuse of antibiotics. Traditional antibiotics bear many limitations, including restricted bioavailability, inadequate penetration and the emergence of antimicrobial-resistant microorganisms. Recent advances in nanotechnology for the introduction of nanoparticles with fascinating physicochemical characteristics have been predicted as an innovative means of defence against antimicrobial-resistant diseases. The use of nanoparticles provides several benefits, including improved tissue targeting, better solubility, improved stability, enhanced epithelial permeability and causes minimal side effects. However, except for gold nanoparticles (AuNPs), the biological safety of the majority of metal nanoparticles remains a serious problem. AuNPs appear to be promising for drug delivery and medicinal applications because of their minimal toxicity, biocompatibility, functional flexibility, chemical stability and versatile biological activities, such as their antiviral, antifungal, anti-inflammatory and antimicrobial properties. Hence, we are focusing on the gold nanoparticles possessing antimicrobial activity in this article. This review will cover recent strategies in the preparation of gold nanoparticles, with special emphasis placed on antibiotics-coated AuNPs with enhanced antimicrobial properties and how they fight against disease-causing bacteria and eradicate biofilms, along with their activities and physicochemical properties.